Extension of the shelf-life of fresh pasta using modified atmosphere packaging and bioprotective cultures - Marzano, Marinella; Calasso, Maria; Caponio, Giusy Rita; Celano, Giuseppe; Fosso, Bruno; De Palma, Domenico; Vacca, Mirco; Notario, Elisabetta; Pesole, Graziano; De Leo, Francesca; De Angelis, Maria (Frontiers in Microbiology, 2022)
Abstract: Microbial stability of fresh pasta depends on heat treatment, storage temperature, proper preservatives, and atmosphere packaging. This study aimed at improving microbial quality and safety and shelf life of fresh pasta by using modified atmosphere composition and packaging with or without the addition of bioprotective cultures (Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium spp., Bacillus coagulans) into semolina. Three fresh pasta variants were made using (i) the traditional protocol, MAP (20:80 CO2:N2) and barrier packaging (control), (ii) the experimental MAP (40:60 CO2:N2) and barrier packaging, and (iii) the experimental MAP, barrier packaging and bioprotective cultures. Their effects on physicochemical properties (i.e., content on macro elements, water activity, headspace O2 and CO2 concentrations, mycotoxins), microbiological patterns, protein and volatile molecules profiles were investigated at the beginning and the end of actual or expected shelf-life through traditional and multi-omics approach. We showed that the gas composition and properties of the packaging material tested in the experimental MAP system with or without bioprotective cultures positively affect the features of fresh pasta without changes on their main chemical properties, which can be stored for longer 120 days at the refrigerated condition. The results demonstrated that bioprotective cultures by their antimicrobials and/or fermentation products synergically controlled the spoilage and the associate food-borne microbiota of fresh pasta during storage, although they were not all able to growth in the tested conditions. The volatile compounds, profiled through gas-chromatography mass-spectrometry (GC-MS), highlighted significant differences deter-mined by the different manufacturing and packaging of samples. Therefore, the use of the proposed MAP system and the addition of bioprotective cultures can be considered a helpful strategy at industrial level to control the quality loss of fresh pasta during refrigerated storage and to increase of 30 days the shelf life of fresh pasta, with potential benefits on the economy and on the environment, spurring innovation in existing production models.